VIBRATIONAL PREDISSOCIATION OF ARH2O - Bissonnette, C; Clary, D (1992)
Accurate close-coupling calculations are used to investigate the vibrational predissociation of ArH2O as a function of the overall rotation J of the van der Waals complex. A full vibrational and rotational basis of H2O states is used in the calculation. The potential energy surface is of a form due to Cohen and Saykally and derived from far-infrared spectra, with an additional term to introduce the dependence on the vibrations of H2O. The linewidths calculated in this work show a maximum at J=6 and it is found that Fermi resonances affect dramatically the magnitude of the calculated linewidths. Good agreement with experimentally measured linewidths of Nesbitt and Lascola is achieved and the calculations provide a simple picture for the J dependence of the linewidths. © 1992 American Institute of Physics.